ANALISIS LAPORAN ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PADA KOPERASI CU. FAOMASI TELUKDALAM PERIODE 2016-2020 - Inez Velda Netta Buluaro (Jurnal Ilmiah Mahasiswa Nias Selatan, 2022)
The problem in this research is cash management in CU Coorperative operations. The formation is less effective because it fluctuates over a certain period. This study aims to analyze cash flow statements to assess financial performance during the 2016-2020 period. The type of research used in this research is qualitative. The data analysis technique used by researchers is to use the cash flow ratio, namely the ratio of operating cash flows to current liabilities, the ratio of operating cash flows to interest, the ratio of operating cash flows to capital expenditures, the ratio of operating cash flows to total debt and the ratio of operating cash flows on net profit. The results of the research on operating cash flow to current liabilities mean value ratio of 1,329 > 1, operating cash flow to interest avarage value is 1,437 > 1, operating cash flow to return on capital avarage value is 0,025 < 1, cash flow operations to total debt the avarage value is 0,024 < 1, and operating cash flow to net income the avarage value is 34,130 > 1. Suggestions for this research are: CU. Faomasi needs to minimize capital expenditures in order to balance the financial performance of the coorperative in covering its interest costs with operating cash flow